Protection of Children's Rights in Fishermen's Workers' Families: The Perspective of KHI and the Child Protection Law - Mukhlis Tri Mulya Marpaung; Ibnu Radwan Siddik Turnip (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
Children in fisherman laborer families in Kurandak Village, Deli Serdang Regency, continue to face serious issues regarding the fulfillment of their fundamental rights, particularly in the areas of education, protection, and care. Normatively, Law Number 35 of 2014 on Child Protection and the Compilation of Islamic Law (KHI) explicitly regulates the responsibilities of parents in fulfilling these rights comprehensively. This study aims to analyze the implementation of child rights protection in fisherman laborer families from the perspective of the Child Protection Law and Islamic legal norms, identify the inhibiting factors, and examine the relevance of the concept of hadhanah in the context of coastal communities. This research employs a qualitative method with a juridical-sociological approach. Primary data were obtained through in-depth interviews with six respondents, consisting of parents, teenagers, children, and community figures. Secondary data were derived from primary legal sources, including Law Number 35 of 2014 and the Compilation of Islamic Law. The findings reveal that children’s rights—particularly the rights to education, protection from labor exploitation, and access to healthcare—are not fully fulfilled. Major obstacles include economic hardship, early work culture, low parental awareness, and lack of government support. This research implies that protecting children's rights in fisherman communities requires a synergistic approach that combines normative legal frameworks and community-based sociological strategies. Local governments and religious institutions must develop educational and mentoring programs rooted in Islamic legal values, particularly hadith, to enhance parental awareness and child welfare